The Influence of Education Level and Accounting Understanding on the Quality of Financial Reports of MSMEs in Negeri Katon District - Nadia Anggraeni; Lella Anitsa; Esty Apridasari; Berwin Anggara (al-Afkar, Journal For Islamic Studies, 2025)
This research examines the influence of education level and understanding of accounting on the quality of UMKM financial reports. This research was conducted in Nageri Katon District using data on the number of UMKM in Negeri Katon District. The sampling method uses purposive sampling, namely using certain criteria to determine the number of samples to be studied. The relationship or influence between variables is explained using descriptive statistical test methods. The research results show that the level of education and understanding of accounting have a significant effect on the quality of UMKM financial reports in Negeri Katon District.